2007
DOI: 10.1159/000099014
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Tubal Heterotopic Pregnancy: Assisted vs. Spontaneous Conceptions

Abstract: Background: It has not been established whether the clinical outcomes of tubal heterotopic pregnancy resulting from assisted conception are different to those of spontaneous conception. The aim of this study was to compare the clinical course and the outcome of intrauterine gestation following surgical treatment for tubal heterotopic pregnancy according to the method of pregnancy. Methods: Medical records of 13 cases of tubal heterotopic pregnancy experienced in Seoul National University Hospital during 1990–2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
8
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 24 publications
6
8
1
Order By: Relevance
“…In our study, a continuing pregnancy in cases of HP was achieved in 93 of 132 patients (70.5%). This was in agreement with a previous report by Han et al ,. who showed that HP after assisted reproductive technology (ART) had better pregnancy outcomes than naturally occurring cases.…”
Section: Discussionsupporting
confidence: 94%
“…In our study, a continuing pregnancy in cases of HP was achieved in 93 of 132 patients (70.5%). This was in agreement with a previous report by Han et al ,. who showed that HP after assisted reproductive technology (ART) had better pregnancy outcomes than naturally occurring cases.…”
Section: Discussionsupporting
confidence: 94%
“…Although a precise aetiology of HP is not known, factors predisposing to HP appear to be identical to those predisposing to ectopic pregnancy (12,13). Assisted reproduction increases the risk of HP because of the highly associated multiple and ectopic pregnancy rates (9,12).…”
Section: Discussionmentioning
confidence: 99%
“…Transvaginal ultrasound or laparoscopic guided aspiration and/or injection of potassium chloride, methotrexate, mifepristone (RU486), prostaglandin or hyper osmolar glucose has been described (12,13,15,18,19). While potassium chloride is nonteratogenic and commonly used, methotrexate, RU486 and prostaglandin are potentially teratogenic and should not be used (12,15).…”
Section: Discussionmentioning
confidence: 99%
“…This is in conformity with authors that reported an increase in and not in uterine twin gestation. In ARTrelated heterotopic pregnancy and an exclusive singleton intrauterine gestations in natural cycle related heterotopic pregnancy [4]. In this case report, heterotopic diagnosis was made at about seven weeks of gestation.…”
Section: Discussionmentioning
confidence: 73%
“…Heterotopic pregnancy which was first described at an autopsy study [3] was hitherto a rarity before the introduction and widespread use of ART. In natural conception cycles low frequency ranging from 1 in 10,000 to 1 in 50,000 was reported and high rates of heterotopic pregnancy from 1 in 100 to 1 in 500 was reported in ART treatment cycles [4][5][6]. The later is attributable to super ovulation induction, multiple embryo transfer with resultant increase in multiple pregnancy and ectopic pregnancy.…”
Section: Discussionmentioning
confidence: 99%